2005
DOI: 10.1074/jbc.m502588200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Shutoff of Phototransduction in Transgenic Mice Expressing Palmitoylation-deficient Rhodopsin*♦

Abstract: Palmitoylation is a reversible, post-translational modification observed in a number of G-protein-coupled receptors. To gain a better understanding of its role in visual transduction, we produced transgenic knock-in mice that expressed a palmitoylation-deficient rhodopsin (Palm ؊/؊ ). The mutant rhodopsin was expressed at wild-type levels and showed normal cellular localization to rod outer segments, indicating that neither rhodopsin stability nor its intracellular trafficking were compromised. But Palm ؊/؊ ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 49 publications
(37 reference statements)
1
45
0
Order By: Relevance
“…Therefore, the shutoff of rhodopsin activation by phosphorylation would be less in the mutant. We tried to experimentally assess the phosphorylation efficiency of the E122Q mutant rhodopsin in knock-in mouse ROS, because phosphorylation efficiency affects the rod photosensitivity (37). Preliminary results by using the methods described in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the shutoff of rhodopsin activation by phosphorylation would be less in the mutant. We tried to experimentally assess the phosphorylation efficiency of the E122Q mutant rhodopsin in knock-in mouse ROS, because phosphorylation efficiency affects the rod photosensitivity (37). Preliminary results by using the methods described in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Depalmitoylation of rhodopsin by chemical treatment with hydroxylamine was extensively used to elucidate the role of palmitoylation (6,10,(25)(26)(27), but the results should be interpreted with caution, especially because high concentrations of this strong nucleophile can produce off-target effects on membrane structures. Expressed in COS cells, bovine opsin mutants containing a serine substitution at Cys-323 showed reduced lightdependent phosphorylation by rhodopsin kinase (9), but subsequent studies employing Cys-322-Thr and Cys-323-Ser knockin mice revealed that, after exposure to light, rhodopsin became phosphorylated at a faster rate in mutant than in WT retinas (11). Conformational changes in the C terminus were observed upon depalmitoylation in biochemical assays (25).…”
Section: Discussionmentioning
confidence: 99%
“…Initial characterization of these Palm −/− mice showed that the mutant rhodopsin became hyperphosphorylated upon light activation, thereby enhancing "shut-off" of rhodopsin (11). Palm −/− mice manifested differences in the rate of transducin activation by rhodopsin and single-molecule force microscopy revealed changes in the force needed to unfold the last stable structural segment of rhodopsin at its carboxyl terminal end (12).…”
Section: Gnat1mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar strategies to evaluate the in vivo importance of specific cysteine oxidation targets are largely lacking, and only a few knock-in mice with mutated cysteine knock-ins have been reported. Rhodopsin is a target for palmitoylation at cysteine residues 322 and 323, and knock-in mice in which these sites were mutated to threonine and serine residues were reported to have enhanced shut-off phototransduction [238]. A mouse containing a single amino acid substitution (Cys249Trp) in the human Crumbs homolog-1 gene displayed in retinal degeneration [239].…”
Section: Assessment Of the Functional Importance Of Cysteine Oxidatiomentioning
confidence: 99%